Drivers and effects of stock market fragmentation - Insights on SME stocks - Jens Lausen; Benjamin Clapham; Peter Gomber; Micha Bender (Leibniz Institute for Financial Research SAFE, 2022)
We analyze how market fragmentation affects market quality of SME and other less actively traded stocks. Compared to large stocks, they are less likely to be traded on multiple venues and show, if at all, low levels of fragmentation. Concerning the impact of fragmentation on market quality, we find evidence for a hockey stick effect: Fragmentation has no effect for infrequently traded stocks, a negative effect on liquidity of slightly more active stocks, and increasing benefits for liquidity of large and actively traded stocks. Consequently, being traded on multiple venues is not necessarily harmful for SME stock market quality.
Keywords: G10; G14; 330; Market Microstructure; Market Fragmentation; Securities Market Regulation; Market Quality; SME Trading